PENGUKURAN MOTIVASI KARYAWAN DENGAN MENGGUNAKAN MULTIDIMENSIONAL WORK MOTIVATION SCALE DAN MOTIVATION AT WORK SCALE (STUDI PADA KANTOR SATUAN POLISI PAMONG PRAJA DI KOTA MAGELANG) - Suryani, Feliana Ade; Perdhana, Mirwan Surya (Faculty of Economics and Business Diponegoro University, 2016)
The aim of this study is to measure employee work motivation at the Satuan Polisi Pamong Praja (Satpol PP) Office in Magelang.Mixed methods approach was utilized in this study. The quantitative instruments were MWMS (Multidimentional Work Motivation Scale) and MAWS (Motivation at Work Scale) while interview was used for the qualitative instrument. The study involves 51 employees as the questionnaire respondents and 5 employees as interviewees.Based on the results of the quantitative and qualitative data, employees of Satuan Polisi Pamong Praja (Satpol PP) in Magelang have medium level of motivation to conduct their job. Implication for theory and practice were discussed.